Cigarette smoking is associated with adverse pathological response and increased disease recurrence amongst patients with muscle‐invasive bladder cancer treated with cisplatin‐based neoadjuvant chemotherapy and radical cystectomy: a single‐centre experience. (8th January 2019) - Boeri, Luca; Soligo, Matteo; Frank, Igor; Boorjian, Stephen A.; Thompson, Robert H.; Tollefson, Matthew; Quevedo, Fernando J.; Cheville, John C.; Karnes, Robert Jeffrey
Abstract : Objective: To investigate the association between smoking status and pathological response to cisplatin‐based neoadjuvant chemotherapy (NAC) and survival outcomes in patients with muscle‐invasive bladder cancer (MIBC) treated with radical cystectomy (RC). Patients and Methods: We reviewed 201 patients treated with NAC and RC for cT2–cT4N0M0 BC between 01/1999 and 01/2015. Smoking status was categorised as: 'never', 'former', and 'current' smoker. Pathological response to NAC was defined as: complete (ypT0N0), partial (ypTis/Ta/T1, N0), and no response (ypT2–4 or ypN+). Clinicopathological characteristics were analysed according to smoking status. Logistic regression analyses tested the association between smoking status and pathological response to NAC. Cox regression analyses tested risk factors associated with recurrence, overall (OM) and cancer‐specific mortality (CSM). Results: Overall, there were 58 (28.9%) never smokers, 87 (43.3%) former smokers, and 56 (27.9%) current smokers. No response to NAC was more frequently noted in current smokers (73.2%; P = 0.007). Former smoker (odds ratio [OR] 2.28; P = 0.024) and current smoker statuses (OR 4.52; P < 0.001) were significantly associated with no response to NAC, after adjusting for age, gender, Charlson Comorbidity Index, and clinical stage. Similarly, current smoking status (hazard ratio [HR] 2.14; P = 0.03) and extravesical pathological tumour stage (HR 3.31; P < 0.001) were independently associated with an increased risk of recurrence after RC. Conclusion: Cigarette smoking was significantly associated with adverse pathological response to cisplatin‐based NAC in patients with MIBC treated with RC. Current smokers were at significantly higher risk of disease recurrence as compared to former and never smokers.